Analisis Pengungkapan Akuntansi Lingkungan Terhadap Pertanggungjawaban Sosial Industri Kimia (Studi kasus Pada Sosial Industri Kimia di Kota Bandar Lampung) - Rosmiaty Tarmizi; Devi Octavianti; Chairul Anwar (Universitas Bandar Lampung (UBL), 2012)
The chemical industry is inseparable from the existing environmental problems and is influenced by several factors. The purpose of this study is to determine whether those factors that exist within the company, which is in the possession of diproksikan management, leverage, the size of the company, affecting the social profitability of a companys disclosure. Disclosure of corporate social pengkomunikasian need to be done as a form of social and environmental impacts of economic activities of the organization with respect to specific stakeholder groups, to the community as a whole. The sample in this research is chemical industry company in Bandar Lampung. In the processing of data of this study, the authors used a CUCKOLD KELLY WELLS with program testing multiple linear regression. From the research we can note that the ownership of the management, the level of leverage, size and profitability of the company, affecting the social accountability.